Exploring the potential central regulatory mechanisms of acupuncture for acute-stage Bell’s palsy: an fMRI-based investigation - Xu, Xiao-shuang; Zhang, Ya-ting; Li, Xiao-wei; Shu, Yu-ling; Zhang, Jing-can; Miao, Ting-ting; Yang, Yan-yan; Yang, Jun; Shi, Hai-ping (Frontiers in Neuroscience, 2025)
ObjectiveThis study utilized resting-state functional magnetic resonance imaging (fMRI) to examine changes in brain functional activity following acupuncture treatment for acute Bell’s palsy (BP) and to investigate the potential central regulatory mechanisms involved.MethodsA total of 55 patients with acute Bell’s facial paralysis (within 1–7 days of onset) were enrolled in the patient group, while 48 individuals without the condition were included as the healthy control group. The patient group received acupuncture therapy at EX-HN16 (Qianzheng), SJ17 (Yifeng), ST2 (Sibai), GB14 (Yangbai), EX-HN4 (Yuyao), SI18 (Quanliao), ST6 (Jiache), ST4 (Dicang), ST8 (Touwei), and bilateral LI4 (Hegu) points on the affected side. Each session lasted 30 min and was administered three times a week (Wednesday, Friday, and Sunday) until day 28 of the disease course. The patient group underwent fMRI scans, House–Brackmann (H-B) grading, Sunnybrook scale evaluation, and facial disability index (FDI) assessment both prior to the initial treatment and on the 28th day. The healthy group received a single fMRI scan after enrollment. MATLAB R2017 software was used to calculate the fractional amplitude of low-frequency fluctuation (fALFF) and regional homogeneity (ReHo) in patients before and after treatment, as well as in healthy controls.ResultsFollowing treatment, the patient group showed significant improvements in H-B, Sunnybrook, and FDI scores compared to pretreatment levels (P < 0.05), with an overall effective rate of 96.4% (53/55). Prior to treatment, compared to healthy controls, patients exhibited decreased fALFF in the right posterior cingulate gyrus, increased fALFF in the right postcentral gyrus, left and right middle frontal gyri, and increased ReHo in the left precentral gyrus, right postcentral gyrus, and left middle occipital gyrus. After treatment, when compared to healthy controls, patients showed decreased fALFF in the left and right medial superior frontal gyri, and increased fALFF in the right postcentral gyrus, left precentral gyrus, and bilateral lingual gyri, and increased ReHo in the right precentral gyrus, bilateral transverse temporal gyri, right lingual gyrus, and right thalamus, and decreased ReHo in the right middle frontal gyrus. Relative to pretreatment values, patients displayed decreased fALFF in the left medial superior frontal gyrus and increased fALFF in the left precentral gyrus. Additionally, ReHo decreased the right and left medial superior frontal gyri, while it increased in the right inferior parietal angular gyrus, right precentral gyrus, and left superior parietal gyrus.ConclusionAcupuncture demonstrates a clear therapeutic effect on acute BP and contribute to clinical symptom improvement. Marked differences in brain functional activity were observed between patients and healthy individuals. The therapeutic effect of acupuncture may be linked to its ability to facilitate functional reorganization in brain regions associated with sensation, movement, and emotion.Clinical trial registrationhttps://www.chictr.org.cn/searchproj.html? title=&officialname=&subjectid=&regstatus=&regno=ChiCTR2200065223& secondaryid=&applier=&studyleader=&createyear=&sponsor=&secsponsor= &sourceofspends=&studyailment=&studyailmentcode=&studytype=&study stage=&studydesign=&recruitmentstatus=&gender=&agreetosign=&measure= &country=&province=&city=&institution=&institutionlevel=&intercode=& ethicalcommitteesanction=&whetherpublic=&minstudyexecutetime=&maxstudy executetime=&btngo=btn, identifier ChiCTR2200065223.